A Analysis of Production Management in Maintaining the Existence of SJ.Sona Jaya Ambulu Products - Putri Nur Indah Sari Putri Nur; Siti Husnul Hotima Siti Husnul Hotima (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research aims to find out the application of production management carried out, as well as to find out what obstacles are faced when carrying out production activities to maintain product existence. This research is a type of qualitative research with a descriptive type, to obtain data and information related to the problems to be studied further, researchers collect data in the form of observation, interviews and documentation. The subjects of this research are the owner and several employees of SJ.Sona Jaya. The object of this research is production management and the obstacles faced in the production process carried out by SJ.Sona Jaya. Based on the results of the study, SJ.Sona Jaya's production management carries out production by implementing four management functions which include planning, organizing, actuating and controlling.